The effect of ginger extract on cisplatin-induced acute anorexia in rats - Kim, Hyeonah; Park, Keun-Tae; Jo, Heejoon; Shin, Yuchan; Chung, Geehoon; Ko, Seong-Gyu; Jin, Young-Ho; Kim, Woojin (Frontiers in Pharmacology, 2023)
Cisplatin is a platinum-based chemotherapeutic agent widely used to treat various cancers. However, several side effects have been reported in treated patients. Among these, acute anorexia is one of the most severe secondary effects. In this study, a single oral administration of 100 or 500 mg/kg ginger extract (GE) significantly alleviated the cisplatin-induced decrease in food intake in rats. However, these body weight and water intake decreases were reversed in the 100 mg/kg group rats. To elucidate the underlying mechanism of action, serotonin (5-HT) and 5-HT2C, 3A, and 4 receptors in the nodose ganglion of the vagus nerve were investigated. The results showed that cisplatin-induced increases in serotonin levels in both the blood and nodose ganglion tissues were significantly decreased by100 and 500 mg/kg of GE administration. On 5-HT receptors, 5-HT3A and 4, but not 2C receptors, were affected by cisplatin, and GE 100 and 500 mg/kg succeeded in downregulating the evoked upregulated gene of these receptors. Protein expression of 5-HT3A and 4 receptors were also reduced in the 100 mg/kg group. Furthermore, the injection of 5-HT3A, and 4 receptors antagonists (palonostron, 0.1 mg/kg, i.p.; piboserod, 1 mg/kg, i.p., respectively) in cisplatin treated rats prevented the decrease in food intake. Using high-performance liquid chromatography (HPLC) analysis, [6]-gingerol and [6]-shogaol were identified and quantified as the major components of GE, comprising 4.12% and 2.15% of the GE, respectively. Although [6]-gingerol or [6]-shogaol alone failed to alleviate the evoked anorexia, when treated together, the effect was significant on the cisplatin-induced decrease in food intake. These results show that GE can be considered a treatment option to alleviate cisplatin-induced anorexia.